Jñāneśvarī-praveśikā - Joshi, Mahadeoshastri Sitaram, 1906- (SAMP early 20th-century Indian books project, 1947)
Introduction to Jñaneśvarī by Jñānadeva, fl. 1290, explaining main subjects with relevant text and comments.